2013
DOI: 10.1016/j.ijgo.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of risk factors for ileus and bowel obstruction following benign gynecologic surgery

Abstract: Lysis of adhesions, concomitant bowel surgery, and perioperative complications such as blood transfusion and cystotomy were found to be risk factors for the development of ileus and/or SBO after benign gynecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…6,12,19e21 In addition, the primary risk factors for SBO identified in our study, namely, cystotomy, adhesiolysis, and blood transfusion, were identified in other studies evaluating SBO after hysterectomy. 9 Patients who experienced SBO were found to have higher complication rates with infectious morbidity, such as surgical site infection and sepsis, occurring more often before a diagnosis of SBO. Because of the limitations of the NSQIP database, direct correlations between surgical site infectious morbidity and early SBO cannot be made; however, surgical site infection has been shown to increase the risk of SBO in other studies.…”
Section: Gynecology Original Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…6,12,19e21 In addition, the primary risk factors for SBO identified in our study, namely, cystotomy, adhesiolysis, and blood transfusion, were identified in other studies evaluating SBO after hysterectomy. 9 Patients who experienced SBO were found to have higher complication rates with infectious morbidity, such as surgical site infection and sepsis, occurring more often before a diagnosis of SBO. Because of the limitations of the NSQIP database, direct correlations between surgical site infectious morbidity and early SBO cannot be made; however, surgical site infection has been shown to increase the risk of SBO in other studies.…”
Section: Gynecology Original Researchmentioning
confidence: 98%
“…Cystotomy, adhesiolysis, postoperative transfusion, and concomitant bowel surgery were identified as independent risk factors for SBO, the majority of which occurred in the first week after surgery. 9 Due to limitations of the study, the authors could not comment on the effect of mode of hysterectomy on the risk of SBO and were unable to describe the incidence and management of early SBO following hysterectomy. Our objective was to determine the incidence, risk factors, and trends in management of early SBO following hysterectomy for benign indications, using a national surgical database.…”
mentioning
confidence: 99%
“…The SCAR studies introduced the use of readmissions and reoperation as an outcome measuring long-term morbidity of adhesions. Most studies on long-term outcomes of adhesions focus on only one single complication, e.g., small bowel obstruction [ 18 , 19 ]. After open gynecological surgery, small bowel obstruction is reported in 7–18% of operations, which is comparable to the 3–14% of adhesions-related readmissions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] In addition to well-established risk factors such as the use of opioid analgesics, specific risk factors for the development of ileus following gynaecologic surgery include the lysis of pelvic adhesions, the presence of a cystotomy, and the concomitant manipulation of the bowel, including reanastomosis. 10 Although standards of care in the postoperative management of patients undergoing abdomino-pelvic surgery have changed significantly over the last few years, several issues remain unresolved. Specifically, the traditional practice of placing postoperative patients on nil-by-mouth orders and routinely placing nasogastric tubes has been questioned in recent studies.…”
Section: Discussionmentioning
confidence: 99%